Sex-Specific Association Between Coronary Artery Disease Severity and Myocardial Ischemia Induced by Mental Stress. Issue 1 (January 2019) - Almuwaqqat, Zakaria; Sullivan, Samaah; Hammadah, Muhammad; Lima, Bruno B.; Shah, Amit J.; Abdelhadi, Naser; Fang, Shuyang; Wilmot, Kobina; Al Mheid, Ibhar; Bremner, J. Douglas; Garcia, Ernest; Nye, Jonathon A.; et al.
ABSTRACT: Objective: It is unclear whether mental stress–induced myocardial ischemia (MSIMI) is related to obstructive coronary artery disease (CAD). We examined this question and contrasted results with ischemia induced by conventional stress testing (CSIMI). Because women are more susceptible to ischemia without coronary obstruction than men, we examined sex differences. Methods: We studied 276 patients 61 years and younger with recent myocardial infarction. CAD severity was quantified using the log-transformed Gensini Score (lnGS) and the Sullivan Stenosis Score. Patients underwent myocardial perfusion imaging with mental stress (public speaking) and conventional (exercise or pharmacological) stress testing. MSIMI and CSIMI were defined as a new or worsening perfusion defect. Results: The prevalence of MSIMI was 15% in men and 20% in women. The median GS for patients with MSIMI was 65.0 in men and 28.5 in women. In logistic regression models adjusted for demographic and cardiovascular risk factors, CAD severity was associated with CSIMI in the full sample (odds ratio [OR] = 1.49, 95% [CI], 1.14–1.95, per 1-unit increase in lnGS), with no significant difference by sex. Although CAD severity was not associated with MSIMI in the entire sample, results differed by sex. CAD severity was associated with MSIMI among men (OR = 1.95, 95% CI, 1.13–3.36, per 1-unit increase in lnGS), but not among women (OR = 1.02, 95% CI, 0.74–1.42, p = .042 for interaction). Analysis using Sullivan Stenosis Score yielded similar results. Conclusions: Findings suggest that CAD severity is related to MSIMI in men but not women. MSIMI in women may therefore be driven by alternative mechanisms such as coronary microvascular disease. Abstract : Supplemental digital content is available in the text.